L'agentivité des portails à l'épreuve des socles figurés des statues des ébrasements - Terrier Aliferis, Laurence (Turnhout : Brepols, 2023)
From the 12th century onwards, portals are privileged spaces to display sculpted decors. In parallel, monumental statues, larger than life, are placed within embrasures. A host of biblical characters as well as ½saints welcome believers within the sacred space and participate to the creation of a specific rhetoric, one visible from outside the building. Some elements, often judged secondary, escaped researcher’s atten-tion. This is true for the figurative pedestals of the statues, which are the subject of this article. These are analysed here by bringing to light three kinds of relationships between the statue and its pedestal: antithetical, exegetical, and annihilated (the relationship is not established with the statue but with adjacent figurative pedestals). Pedestals are therefore actors within the global rhetoric of the portals and their semiology is proven to be significant.
Keywords: Rhetoric of Gothic portals; Figurative pedestals; Marmosets; Jamb statues; Agency